Inside Cover: Theoretical Investigation on the Reaction Pathways of the Oxygen Reduction Reaction on Graphene Codoped with Manganese and Phosphorus as a Potential Nonprecious Metal Catalyst (ChemCatChem 21/2016). Issue 21 (8th November 2016) - Bai, Xiaowan; Zhao, Erjun; Li, Kai; Wang, Ying; Jiao, Menggai; He, Feng; Sun, Xiaoxu; Yang, Jucai; Wu, Zhijian
Abstract : The Cover shows the kinetically most favorable pathway for the hydrogenation of OOH to form O+H2 O in the oxygen reduction reaction (ORR), which is a desired four‐electron process. The development of a high performance catalyst for ORR in fuel cells is a hot topic, highlighted with Chinese Red, in the field of energy and environmental science.In their Full Paper, X. Bai et al. demonstrate the application of spin‐polarized density functional theory for the design of a MnP codoped graphene electrocatalyst as a non‐precious metal alternative for ORR at the cathode in fuel cells. More information can be found in the Full Paper by X. Bai et al. onpage 3353 in Issue 21, 2016 (DOI:10.1002/cctc.201600838 ).